Varicella Zoster Meningitis, Optic Neuritis Preceding the Development of Posterior Outer Retinal Necrosis, and Central Retinal Artery Occlusion in a HIV Patient - Manasa Gunturu; Shiva Kumar Gosi; Swetha Kanduri; Vishnu Garla (Case Reports in Medicine)
Varicella-zoster virus (VZV) has been known to cause various eye disorders in both immunocompetent and immunocompromised patients. We present a case of a forty-nine-year-old female patient with acquired immunodeficiency syndrome (AIDS) who presented with headache, fever, and blurred vision. Cerebrospinal fluid (CSF) analysis was consistent with VZV meningitis. Magnetic resonance imaging (MRI) of the brain showed enhancement of the right optic nerve indicative of optic neuritis. She responded well to acyclovir and steroids and discharged on the same. Four weeks after discharge, she presented with sudden onset blindness in the left eye. A cerebral angiogram revealed left retinal artery occlusion and was treated with tissue plasminogen activator (tPA). Funduscopic examination showed patchy areas of necrosis in the periphery which were rapidly progressive, diagnostic of posterior outer retinal necrosis (PORN). She was started on ganciclovir and cidofovir and experienced significant improvement in her visual acuity.